Challenges for Pedagogical Effectiveness in an Ever-Changing Education Landscape: Conceptualisation of Pedagogical Mobility and Flexibility as a Context-Consciousness - Anna Elizabeth du Plessis; Elize Küng; Elize du Plessis (Education Sciences, 2024)
The challenges to maintaining pedagogical effectiveness in an ever-changing education landscape not only turn focus on the professional development of teachers and their teaching practices but also emphasise the preparation of pre-service teachers and their skill development to practice pedagogical flexibility and mobility while focusing on context-consciousness [...]